2012
DOI: 10.1007/s00109-012-0972-2
|View full text |Cite|
|
Sign up to set email alerts
|

The inhibitory effect of chimeric decoy oligodeoxynucleotide against NF-κB and Sp1 in renal interstitial fibrosis

Abstract: The pathophysiology of chronic renal disease is characterized by a progressive loss of renal function and deposition of the extracellular matrix, leading to widespread tissue fibrosis. Much of the matrix in chronic renal disease is synthesized by interstitial myofibroblasts, recruited from resident fibroblasts and circulating precursors. These changes are believed to be derived from epithelial-mesenchymal transition (EMT) of tubuloepithelial cells. To develop a novel therapeutic approach for treating renal fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…H&E, Masson’s Trichrome, and immunohistochemical staining were performed according to the described procedure 40 . Sections were stained with H&E and Masson’s Trichrome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…H&E, Masson’s Trichrome, and immunohistochemical staining were performed according to the described procedure 40 . Sections were stained with H&E and Masson’s Trichrome.…”
Section: Methodsmentioning
confidence: 99%
“…investigated that TGF-β type I receptor antisense ODN mediates knockdown of TGF-β1 signaling cascades. Kim et al 40 . found that chimeric decoy ODN affects renal interstitial fibrosis via the inhibition of both nuclear factor κB (NF-κB) and Sp1 transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Their sequences are as follows70: w-NF-κB-ODN 5 ′ -GAA ATT TCA GGG AAA TCC CTT CAA GAA AAC TTG AAG GGA TTT CCC T-3 ′ ; m-NF-κB-ODN, 5 ′ -GAA ATT TCA GGG AAA TTA CTT CAA GAA AAC TTG AAG TAA TTT CCC T-3 ′ . These ODN were annealed for 8 h, while the temperature decreased from 80 °C to 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have demonstrated the feasibility of chimeric decoy ODN targeting simultaneously for NF-κB and E2F, NF-κB and E26 Ets, AP-, and Smad, NF-κB and Sp1, and Smad and Sp1 in inflammation and fibrotic lesions of various tissues [51,148,149,150,151,152,153]; it is expected that these results will extend to vascular fibrosis.…”
Section: Decoy Odn Strategy For Vascular Diseasementioning
confidence: 99%